Problems of Staff Development Efficiency in Information Technology Organizations of the Republic of Armenia - Hakobjanyan, Anna; Mirzoyan, Narine (Bulletin of Yerevan University G: Economics, 2021)
The article aimed to study the issues of assessing the effectiveness of personnel development in IT organizations and its relationship with reducing turnover and training highly qualified personnel. The article analyzes the reasons for the change in the structure of the IT sector in the Republic of Armenia, provides a comparative analysis of outsourcing and product organizations. Motivational tools used in the field of information technology are analyzed, assessment of the effectiveness of personnel development of selected local and foreign organizations, based on surveys, is presented, factors influencing the latter are identified.
Keywords: IT companies; outsourcing; product companies; staff turnover; personnel development model